Analisis Dampak Lalu Lintas Swiss-belhotel Kota Pontianak - Sugasta, Hervian Handika; Cahyadi Saputra, Doddy; Adibah, Fairuz; Puji Santosa, Dimas; Rangga, Boy (Jurnal Tekno, 2025)
Traffic Impact Analysis involves assessing the effects caused by traffic resulting from the development of a particular area on the nearby transportation system. This study aims to evaluate the performance of road sections around the Swiss-Belhotel Pontianak vicinity. To achieve the goals and objectives of the study, it is necessary to develop a methodology that can systematically integrate all stages of the work process. Primary data is defined as data obtained through direct measurement or observation at the study location. Meanwhile, secondary data refers to data collected from other parties (individuals, agencies, institutions) without the need to conduct direct measurements or observations on-site. Based on the analysis results above, the performance of the existing road segments (weekend) shows the highest Volume to Capacity Ratio (VCR) on Pahlawan Street, reaching 1.02, with a Level of Service (LoS) of F. Meanwhile, the existing road performance in (weekday) indicates that the highest VCR is on Gajahmada Street, reaching 1.40, also with a Level of Service F. Based on the analysis, it can be concluded that due to the large number of road segments with poor Level of Service (LoS), several Do-Something scenarios need to be implemented to improve the LoS after the existing year. In this study, several recommendations are proposed to enhance the LoS, such as installing additional traffic signs and road markings or widening certain road segments.